Easy preparation of a liposome-mediated protein delivery system by freeze–thawing a liposome–protein complex. Issue 35 (4th May 2022) - Koide, Hiroyuki; Ochiai, Hiroki; Suzuki, Hikaru; Hirata, Shinya; Watanabe, Midori; Yonezawa, Sei; Dewa, Takehisa; Oku, Naoto; Asai, Tomohiro
Abstract : An easy one-step method for the encapsulation of proteins into liposomes based on freeze–thawing a protein–liposome complex was developed for efficient protein delivery. Abstract : Homeostasis can be achieved by adding a protein supplement; however, an appropriate vector is required to deliver the protein into the cell because of the low stability of proteins in the blood and low cell membrane permeability. Here we report an easy one-step method of encapsulating proteins into liposomes for delivery. We used negatively charged superoxide dismutase (SOD) and a polycation liposome as protein and liposome models, respectively. Liposome-encapsulated SOD was prepared by freeze–thawing the SOD–liposome complex (lipoplexes). The amount of immobilized SOD within the lipoplex significantly increased on freeze–thawing. Surprisingly, subjecting the single-layered lipoplexes to freeze–thawing produced multilayered liposomes with SOD localized between the lipid layers. The amount of SOD delivered intracellularly significantly increased by freeze–thawing compared with that delivered by lipoplexes without freeze–thawing. SOD, liposomes, and endosomes were separately localized in the cells. The freeze–thawed lipoplex-encapsulated SOD samples were intravenously injected in mice. The SOD biodistribution was dramatically changed compared with the injection of free SOD or lipoplex. SOD was detached from the lipoplex in the bloodstream after the injection of non-freeze–thawed lipoplex, whereas the encapsulation of SOD in the liposomes upon freeze–thawing enabled the stable circulation of SOD with the liposomes in the bloodstream. This work paves the way for the application of the freeze–thawing technology for the easy one-step encapsulation of proteins into liposomes for protein delivery.